Violence in European schools: victimization and consequences - Andreas Ammermüller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Violence at schools is a well-known problem in many societies. This paper assesses the degree of school violence in 11 European countries and analyzes the determinants of being a victim and its effect on student performance. The study draws on the international TIMSS 2003 and the British longitudinal NCDS data. The level of school violence is high in most countries but seems not to increase over time. Besides gender, social and migration background and the appearance of students determine being bullied, hurt or stolen from by fellow students. Being a victim has a small but significantly negative impact on contemporary and later student performance and the level of educational attainment and thereby affects earnings. It is hence an important peer effect that should not be omitted in the estimation of educational production functions.
Keywords: Z13; I21; J24; 330; School violence; bullying; human capital; TIMSS; NCDS